2018
DOI: 10.3390/toxins10040140
|View full text |Cite
|
Sign up to set email alerts
|

“Appropriate Treatment” and Therapeutic Window in Spasticity Treatment with IncobotulinumtoxinA: From 100 to 1000 Units

Abstract: Many neurological diseases (ischemic and hemorrhagic stroke, multiple sclerosis, infant cerebral palsy, spinal cord injuries, traumatic brain injury, and other cerebrovascular disorders) may cause muscle spasticity. Different therapeutic strategies have been proposed for the treatment of spasticity. One of the major treatments for tone modulation is botulinum toxin type A (BTX-A), performed in addition to other rehabilitation strategies based on individualized multidisciplinary programs aimed at achieving cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In this study, 155 subjects were enrolled, but only 11 (7.1%) suffered from traumatic brain injury [38]. The remaining two investigations did not report the number of spastic subjects according to aetiology [39] or spasticity aetiology [29]. Since these studies had mixed samples, the investigation by Ianieri et al was described in the stroke paragraph and that by Kirshblum et al was reported in the paragraph concerning studies with mixed samples.…”
Section: Brain Injurymentioning
confidence: 97%
See 4 more Smart Citations
“…In this study, 155 subjects were enrolled, but only 11 (7.1%) suffered from traumatic brain injury [38]. The remaining two investigations did not report the number of spastic subjects according to aetiology [39] or spasticity aetiology [29]. Since these studies had mixed samples, the investigation by Ianieri et al was described in the stroke paragraph and that by Kirshblum et al was reported in the paragraph concerning studies with mixed samples.…”
Section: Brain Injurymentioning
confidence: 97%
“…The group treated by incoBTX-A > 700 U was injected by progressively increasing dosages, with a mean dose between 775.65 ± 30.45 and 986.65 ± 13.67 U. Transient general weakness was observed in 4% of subjects [39].…”
Section: Incobotulinumtoxina (Xeomin)mentioning
confidence: 99%
See 3 more Smart Citations